Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 201091 by MrGHK last updated on 29/Nov/23

Commented by Frix last updated on 29/Nov/23

Look at the first few summands:  i=0 → 1  i=1 → (n/(2n+4))  i=2 → ((n^2 −n)/(6n+24n+24))  i=3 → ((n^3 −3n^2 +2n)/(24n^3 +144n^2 +288n+192))  i=k → (n^k /((k+1)!n^k +...))  The limit_(n→∞)  of the summands for i=k is (1/((k+1)!))  The sum then is Σ_(k=0) ^∞  (1/((k+1)!)) =e−1

Lookatthefirstfewsummands:i=01i=1n2n+4i=2n2n6n+24n+24i=3n33n2+2n24n3+144n2+288n+192i=knk(k+1)!nk+...Thelimitnofthesummandsfori=kis1(k+1)!Thesumthenisk=01(k+1)!=e1

Commented by MrGHK last updated on 29/Nov/23

very great

verygreat

Answered by witcher3 last updated on 29/Nov/23

Σ_(i=0) ^n ((1/(n+2)))^i .((n!)/((n−i)!.i!(i+1)))  Σ_(i=0) ^n .( ((n),(i) )/((n+2)^i (i+1)))  (1+x)^n =Σ_(i=0) ^n  ((n),(i) ).x^i ⇒∫_0 ^t (1+x)^n dx=Σ_(i=0) ^n ( ((n),(i) )/(i+1))t^(i+1) =(((1+t)^(n+1) −1)/(n+1))  ⇒Σ_(i=0) ^n ( ((n),(i) )/(i+1))((1/(n+2)))^i =(((1+(1/(n+2)))^(n+1) −1)/((n+1)))(n+2)  =(e^((n+1)((1/(n+2))−(1/(2(n+2)^2 ))+o((1/n^2 )))) /1).((n+2)/(n+1));((n+2)/(n+1))∼1  ∼(e^(1−(1/(2(n+2)))+o((1/(n )))) −1)∼e−1  lim_(n→∞) .((n!)/((n−i)!.(i+1).(n+2)^i ))=e−1

ni=0(1n+2)i.n!(ni)!.i!(i+1)ni=0.(ni)(n+2)i(i+1)(1+x)n=ni=0(ni).xi0t(1+x)ndx=ni=0(ni)i+1ti+1=(1+t)n+11n+1ni=0(ni)i+1(1n+2)i=(1+1n+2)n+11(n+1)(n+2)=e(n+1)(1n+212(n+2)2+o(1n2))1.n+2n+1;n+2n+11(e112(n+2)+o(1n)1)e1limn.n!(ni)!.(i+1).(n+2)i=e1

Commented by MrGHK last updated on 29/Nov/23

very nice solution

verynicesolution

Terms of Service

Privacy Policy

Contact: info@tinkutara.com